1985
DOI: 10.1677/joe.0.1050323
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the genital tract and plasma levels of oxytocin and cortisol at the time of mating in the ewe

Abstract: Experiments were conducted in the ewe to determine the effects of mating on the activity of the genital tract and on blood levels of oxytocin and cortisol. The activity of the uterus and cervix was recorded by electromyography, oxytocin was measured by radioimmunoassay, and cortisol by high performance liquid chromatography. Mating itself did not increase circulating oxytocin or cortisol; uterine motility remained unchanged during and after copulation but the cervix was significantly stimulated during teasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Because AI was performed using a catheter empty of semen, it is concluded that these endocrine responses were due to environmental and genital stimuli associated with the handling of animals and the AI procedure only. By comparison, earlier studies in the same species had reported that stimuli associated with mating, such as olfactory, visual and tactile signals, and then coitus did not modify plasma levels of CORT and OT [12,26].…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Because AI was performed using a catheter empty of semen, it is concluded that these endocrine responses were due to environmental and genital stimuli associated with the handling of animals and the AI procedure only. By comparison, earlier studies in the same species had reported that stimuli associated with mating, such as olfactory, visual and tactile signals, and then coitus did not modify plasma levels of CORT and OT [12,26].…”
Section: Discussioncontrasting
confidence: 65%
“…However, it is also well established that strong peristalsis does not facilitate sperm transport, but often reduces fertility [22,25]. Indeed, the uterus responds to mating by increasing its contractile rate, but only transiently, for less than 1 min in the ewe [12,42] and macaque [14,44], or for no longer than 2 min in the rabbit [11] and woman [10]. Therefore, it is tempting to speculate that a secretion of OT altering the contractile rate of the uterus for a long period is detrimental to fertility in a number of species, including the ewe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations